Affixation System in Penglipuran Dialect: A Descriptive Study of Derivational and Inflectional Processes - Wikajaya, I Wayan; Budasi, I Gede; Suarnajaya, I Wayan (Universitas Pendidikan Ganesha, 2018)
AbstractThis study aimed at describing the prefixes and suffixes in Penglipuran Dialect which belong to derivation and inflection. This research was a descriptive qualitative research. The data were collected using three techniques, namely observation, recording technique, and interview (listening and noting) technique. Three informants sample from Penglipuran were chosen based on criteria. The criteria of the informants are: they are smart, they have communicative competence, they have enough knowledge about the topic, they are the native speakers of the Penglipuran village, they are patient, they have high-attention, they have enough time to be interviewed, they are not having disturbances related to speech organs, they are a good listener, they are able to answer the questions, they are confident and they are proud of their language and culture. The results of the study showed that there were six kinds of prefixes in Penglipuran Dialect such as prefix mə-, m-, n-, ŋ-, ñ-, and ə- and there were three kinds of suffixes in Penglipuran Dialect such as -Λŋ, -In and, -ɔ. Prefixes and suffixes in Penglipuran Dialect which belong to derivation were prefix mə- and m- and suffix -Λŋ and -Ιn. Prefixes and suffixes in Penglipuran Dialek which belong to inflection were prefix n-, ŋ-, ñ-, m-, and ə- and suffix -ɔ, -Λŋ, and -In. Key Words: affixation, Penglipuran Dialect, derivational and inflectional processes